PENGARUH TAX AVOIDANCE, RELATED PARTY TRANSACTION DAN VARIABEL KEUANGAN TERHADAP NILAI PERUSAHAAN - Shania Roselina; Annisa Kanti (E-Jurnal Akuntansi TSM, 2022)
The purpose of this study was to determine which the variable that consists of tax avoidance, related party transaction and financial variable has an effect on firm value in non-financing companies listed in Indonesia Stock Exchange. The independent variable used is tax avoidance which is measured using the effective tax rate (ETR) and the related party transaction variable which is measured using a receivable related party. The dependent variable used in this research is firm value which is measured using price book value (PBV). Sample of this research are 85 non-financing companies from 2016 to 2018. The research method is causal study with a sample of companies selected using purposive sampling. Data were analyzed by using multiple linear regression analysis method. The results showed that the return on assets and debt to asset ratio significantly had a positive effect on firm value. Meanwhile, tax avoidance has a significant negative effect on firm value. In other hand, the variable current ratio, firm size, dividend payout ratio, investment decisions, and related party transactions have no significant effect on firm value.